2014
DOI: 10.2146/ajhp130202
|View full text |Cite
|
Sign up to set email alerts
|

Medicare annual wellness visits conducted by a pharmacist in an internal medicine clinic

Abstract: A Medicare AMV administered by a CPP resulted in a wide variety of patient interventions and reimbursement for services provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…3 Research has begun to explore the feasibility of alternative care models in which the AWV is led by nonphysician health professionals, including pharmacists. [4][5][6][7] Preliminary work has described the pharmacistled AWV and demonstrated the financial implications of the AWV for pharmacists in primary care settings. [5][6][7] Park et al showed that AWVs provide a way for pharmacists to support their salary in a physician's office.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Research has begun to explore the feasibility of alternative care models in which the AWV is led by nonphysician health professionals, including pharmacists. [4][5][6][7] Preliminary work has described the pharmacistled AWV and demonstrated the financial implications of the AWV for pharmacists in primary care settings. [5][6][7] Park et al showed that AWVs provide a way for pharmacists to support their salary in a physician's office.…”
mentioning
confidence: 99%
“…One study briefly detailed the interventions made by a pharmacist during an AWV. 5 Perceived barriers to the pharmacist-led AWV include lack of patient acceptance and physician support; however, there is no current information published assessing patient or physician satisfaction with the pharmacist-led AWV.…”
mentioning
confidence: 99%
“…Each visit lasted a mean of 73 minutes, and 4.5 interventions were made per patient during the encounter [10]. Interventions included referrals to other providers such as nutritionists and physical therapists; education interventions about topics such as advance directives and home safety; laboratory tests; immunizations; and medication initiation [10].…”
Section: Annual Wellness Visitsmentioning
confidence: 99%
“…Oral chemotherapy services, wellness services, cognitive memory screening, psychotherapy, pharmacogenetic testing, health education, concordance, counselling, medication therapy management (MTM), follow-up and referral services Determine educational and training opportunities for community pharmacists, thereby improve patient-centred experiences that supplement their confidence, knowledge, and skill in providing advanced pharmacy services [35][36][37][38][39][40][41][42][43][44][45][46] Surgical department Cardiopulmonary resuscitation (CPR) Determine pharmacist participation on CPR teams in health care delivery organizations [47,48] Regulatory scrutiny Drug Pricing Evaluate and monitor drug pricing through the use key metrics on cost savings achieved, maintenance costs, and other aspects of program involvement [49] In-patient Pharmaceutical care Provision of pharmaceutical care, identification of drug therapy problems, prevention of adverse drug reactions and monitoring of drug therapy management [48,50,51] Out-patient department Ambulatory care, patient education Assertively advancing ambulatory care practice, to achieve the national priorities of improving patient care, adherence, patient health, and affordability of care [48,52,53] Pediatric department Pediatric care Provision of advanced pediatric care [48,54] Intensive care units and oncology department Palliative care services Introducing the concept of 'advanced practice roles' in pharmacy within the new integrated regionalized palliative care service [48,55,56] …”
Section: Peculiar Advanced Pharmacy Practice Servicesmentioning
confidence: 99%